Feldtheoretische Aspekte in der Ethnopsychoanalyse von Georges Devereux - Danielle Bazzi (Swiss Journal of Sociocultural Anthropology, 2015)
This article demonstrates the methodological and epistemological relevance of Georges Devereux’ use of field theory as a method in the sense of a contribution to the current discussion in social anthropology about the decentering of the anthropocentric understanding of the subject. Devereux’ complementary approach enables – but is also an obligation – not just to change the "either/ or" of culture and nature into an "as well as", but to accept it as a perennial construction of boundaries.